Solid lipid nanoparticles (SLN) - based hydrogels as potential carriers for oral transmucosal delivery of Risperidone: preparation and characterization studies - Silva, Ana Catarina (2021)
Two different solid lipid nanoparticles (SLN)-based hydrogels (HGs) formulations were developed as potential mucoadhesive systems for risperidone (RISP) oral transmucosal delivery. The suitability of the prepared semi-solid formulations for application on oral mucosa was assessed by means of rheological and textural analysis, during 30 days. Plastic flows with thixotropy and high adhesiveness were obtained for all the tested systems, which predict their success for the oral transmucosal application proposed. The SLN remained within the colloidal range after HGs preparation. However, after 30 days of storage, a particle size increase was detected in one type of the HGs formulations. In vitro drug release studies revealed a more pronounced RISP release after SLN hydrogel entrapment, when compared to the dispersions alone. In addition, a pH-dependent release was observed as well. The predicted in vivo RISP release mechanism was Fickian diffusion alone or combined with erosion.